Integrating Management Accounting and Business Analytics to Improve Innovation Capability - Abdul Madjid (PT. BATARI EDU CALYA, 2026)
The integration of management accounting and business analytics has emerged as a critical strategic imperative for enhancing organizational innovation capability in the contemporary business environment. This study investigates the synergistic relationship between management accounting practices, business analytics capabilities, and innovation performance within the Malaysian context. Drawing upon the resource-based view and dynamic capabilities theory, this research examines how Malaysian organizations can leverage the combined potential of strategic management accounting techniques and advanced data analytics to foster innovation outcomes. The methodology employs a quantitative approach utilizing structural equation modeling (SEM) and partial least squares (PLS) analysis to empirically test the proposed theoretical framework. Results indicate that management accounting practices significantly influence organizational capabilities, while business analytics capabilities serve as critical mediators in the relationship between organizational resources and innovation performance. The findings reveal that Malaysian firms demonstrating higher levels of strategic management accounting adoption and business analytics integration exhibit superior innovation capabilities. This study contributes to the existing literature by providing empirical evidence on the complementary roles of management accounting and business analytics in driving innovation within emerging market contexts, offering practical implications for Malaysian enterprises seeking to enhance their competitive positioning through innovation-driven strategies.